Management and financial performance of agricultural cooperatives: a case of Portuguese olive oil cooperatives - Rebelo, João Fernandes; Leal, Carmem Teresa; Teixeira, Ânia (REVESCO. Revista de Estudios Cooperativos, 2016)
In Portugal, as in other countries, agricultural cooperatives have an important economic role in the food system. Similar to other economic organisations, agricultural cooperatives have witnessed structural changes in recent decades in terms of governance and/or management models. Portuguese agricultural cooperatives have been compelled by their context to adopt a traditional model of ownership and control. The main goal of this study was to analyse issues related to the management structure and financial performance of cooperatives, based on data collected for olive oil cooperatives located in the northern interior region of Portugal. Combining a qualitative analysis of structure and decision-making, a financial assessment and the application of a multi-criteria approach (PROMETHEE II), the overall results are in line with expectations (e.g. low levels of member participation, nonprofessional management, low profitability ratios, low leverage and an ability to fulfil financial commitments), except for the relationship between professional management and financial performance. The existence of professional management does not lead to better financial performance. This result reinforces the belief that cooperatives that are structured differently have different and conflicting stakeholder interests